Incorporating optimisation technique into Zadeh’s extension principle for computing non-monotone functions with fuzzy variable - Muhammad Zaini, Ahmad; M. K., Hasan (Penerbit Universiti Kebangsaan Malaysia (UKM), 2011)
Link to publisher's homepage at http://www.ukm.my/